An Example of the Relationship between Metaphysics and Logic: Genus (Jins) and Differentia (Fasl) as the Parts of Quiddity (Mahiyya) in Ibn Sina and Fakhr al-Din al-Razi’s Thought - Sacide Ataş (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
Beyond being a tool of science, logic is also a specific discipline in Islamic studies that reflects scholars’ metaphysical and ontological assumptions. One feature that best reflects the perceptions of scholars who use logic as a scientific tool is the parallelism between matter-form (mādda-ṣūra) and genus- differentia (jins-faṣl). Genus-differentia are the reflections of the Avicennian matter-form theory in epistemology. In this article, I examine how Ibn Sīnā approached the relationship between genus-differentia and matter-form by accepting the matter-form ontology. Moreover, I analyze how Fakhr al-Dīn al-Rāzī, by applying an atomic ontology, explained genus-differentia in contrast to the matter-form theory.